If it's not what You are looking for type in the equation solver your own equation and let us solve it.
z in (-oo:+oo)
6*z = (1/26)/1 // - (1/26)/1
6*z-((1/26)/1) = 0
6*z-1/26 = 0
6*z-1/26 = 0 // + 1/26
6*z = 1/26 // : 6
z = 1/26/6
z = 1/156
z = 1/156
| 12b+75=20b | | 3r=4.62 | | T-3/8 | | 6x+9=4x+35 | | 5(1+4)=2(3+10m) | | 150m-125m+38600=41000-175m | | 3x+3y-ax-ay=0 | | p/3=4.26 | | 21.3+1x=30. | | 19-(2x+3x)=2(x+3)+x | | N+3=53-n | | 2.1=b-3 | | 221.3+1x=30. | | 4y+7=3y-6 | | 221.3+1x=30 | | 2.83=u-3 | | 2/3y=-5 | | H/2+H/3=20 | | 250/5/10*2 | | 4d+15s-1= | | 9(c-9)=6(2c-12)-4c | | 15+2x=-9 | | -13g/4=9 | | 2+2m=6m-9 | | 4(x-3)+2x-1=(2x-3)+4 | | px+q=r | | -55+32= | | 3(1+2x)-4x=-(x-30) | | G-13/4=9 | | 3h-4(1.5h-3)=1.5h-6 | | 4(3a-2)=16a | | 8-1/3x=17 |